New Public Service Sebagai Paradigma Administrasi Publik Pengawasan Obat dan Makanan - Alexander Arie Sanata Dharma (Eruditio : Indonesia Journal of Food and Drug Safety, 2022)
Indonesia's administration experienced big-bang decentralization during the reform period, with its major milestone being Regional Autonomy. One of the follow-ups to the Law is establishing several Non-Departmental Government Agencies in 2001, one of which is the Indonesian Food and Drug Authority (BPOM). BPOM is a central agency with apparatuses in 33 provincial capitals and 40 districts/cities. Road Map of Bureaucratic Reform 2020-2024 mentions that Indonesia manages three paradigms of public administration in parallel, ranging from Weberian to New Public Service. NPS comes as a criticism of the Old Public Administration and New Public Management, whose primary focus is citizens. This research uses a qualitative approach to place NPS in drug and food surveillance in Indonesia, whose function is run by BPOM.  NPS consists of 7 main principles, and each has conformity with the implementation of drug and food supervision in Indonesia. The circulation of commodities such as Drugs cannot be viewed as limited to NPM considering that in addition to BPOM as a service provider and the pharmaceutical industry as a service recipient, there are also people who will directly impact drugs and food circulating in Indonesia. Based on this conformity, it is recommended that BPOM emphasize the significance of the NPS paradigm as a public administration perspective embraced by the organization and contain it on organizational documents so that stakeholders understand BPOM's performing patterns and the concurrent public administration paradigm.